Perceived Parenting Styles, Emotional Intelligence and Conflict Resolution Styles among Young Adults - Tahir, Zoonash; Quratulain, Ansa (International Journal of Psychology, 2024)
Purpose: Parenting styles greatly influence the development of emotional intelligence and conflict resolution styles among young adults since the very early years of their lives. The understanding how parenting styles and emotional intelligence impact conflict resolution styles of young adults has become progressively urgent. The existing study purposes to inspect the relationship between perceived parenting styles, emotional intelligence, and conflict resolution styles among young adults. The practical implication of this research will provide the future generations in better upbringing of their children that possess high levels of emotional intelligence. Methodology: The study was carried out in a single phase. The study was quantitative, and it was conducted to assess the perceived parenting styles by young adults including assessing their emotional intelligence and identifying their conflict resolution style. The sample of the study was 280 (M=140, F=140) recruited from different universities in Islamabad, Pakistan. Three scales were used for assessment: The Perceived Parenting Styles Scale (PPSC), The Schutte Self Report Emotional Intelligence Test (SSEIT) and the Conflict Resolution Styles Inventory (CRSI). Findings: The authoritative parenting style positively correlated with emotional intelligence (r = .47, p < .01) and positive problem-solving (r = .17, p < .01), while negatively relating to conflict engagement (r = -.31, p < .01) and self-protection (r = -.26, p < .01). In contrast, authoritarian and permissive styles were negatively related to emotional intelligence (r = -.13 and r = -.19, respectively) and positively associated with conflict engagement. Males scored higher on emotional intelligence (M = 121.96, SD = 13.73) than females (M = 118.35, SD = 15.87), and PhD students exhibited higher conflict resolution scores than Master's and undergraduate students. These findings highlight the impact of parenting styles on emotional intelligence and conflict resolution skills among young adults. Unique Contributions to Theory, Practice and Policy: The study is guided by The Social Learning Theory by Bandura (1977) sets that young adults copy ways of behaving gained from their childhood, particularly from their parents. Parenting styles perceived during childhood and adolescence could impact how people approach conflicts and social interactions. Another theory which backs this study is Emotional Intelligence theory by Daniel Goleman suggests that individuals consist of a bunch of skills and abilities that would help them in recognizing, understanding and managing their own self emotions as well as emotions of other people. The study recommends that research be conducted in other demographic regions or on a broader level. The study also recommends that other variables such as personality traits and changes over tine should be considered as well for better outcomes.